FRI0408 Antiphospholipid Antibodies and the Risk of Damage Accrual in Systemic Lupus Erythematosus. (9th June 2015) - Taraborelli, M.; Leuenberger, L.; Lazzaroni, M.G.; Martinazzi, N.; Zhang, W.; Salmon, J.; Franceschini, F.; Tincani, A.; Erkan, D.
Abstract : Background: The effect of antiphospholipid antibodies (aPL) on organ damage in Systemic Lupus Erythematosus (SLE) patients remains unclear as there is a limited number of studies with contrasting conclusions. Objectives: The aim of this study was to assess the relative contribution of aPL to organ damage in SLE patients. Methods: SLE patients (based on American College of Rheumatology [ACR] Classification Criteria) with less than 10 years of disease duration at registry entry were identified from the SLE registry of two centers. Clinical information retrieved included: demographics, disease duration, organ damage assessed by the Systemic Lupus International Collaborating Clinics/ACR Damage Index (SDI), and aPL profile. A "clinically significant" aPL profile was defined as: positive lupus anticoagulant test, anticardiolipin antibody IgG/M >40 GPL or MPL, and/or anti-β2 Glycoprotein-I IgG/M > the 99th percentile), on two or more occasions, at least 12 weeks apart, within ±1 year of registry entry. The outcome variables were any increase of SDI at 5, 10 and/or 15 years of follow-up (time 0 was defined as registry entry). For univariate analysis the demographic and clinical characteristics of patients with and without a SDI increase at 5, 10 and 15 years were compared (Chi square or Fisher's exact test for categorical data, Student t test or Mann-Whitney-Wilcoxon for continuous data as appropriate). The Generalized Estimated Equations (GEE) model was used as multivariate analysis to detect significant factors for increased SDI at 5, 10 and/or 15 years. Results: We identified 262 patients with less than 10 years of disease duration, at least 5 years of prospective follow-up and a complete aPL profile (76% Caucasian, 8% African-American, 6% Asian, and 86% female). Mean age at diagnosis was 31 years (±12) and mean age at registry entry was 33 years (±12) with a mean disease duration of 1 year (±2). Eighty-eight (33%) patients had a clinically significant aPL profile. Twenty-one percent, 42%, and 57% of patients had new organ damage in 5, 10, and 15 years, respectively (Table I ). On the univariate analysis: a) a significant aPL profile (p:0.02) and a older age at diagnosis (p:0.04) were significantly associated to any increase of SDI at 5 years; b) a shorter disease duration was significantly associated to any increase of SDI at 10 years (p:0.003) and 15 years (p:0.008); and c) male gender showed a tendency for any increase of SDI at 15 years without reaching significance (p:0.054). The GEE model showed that patients with a significant aPL profile (p:0.006, Odds Ratio, [OR]:1.9, 95% Confidence Interval, [CI]:1.2-3.1), older age at diagnosis (p:0.007, OR: 1.02, 95%CI 0.006-0.04) or male sex (p:0.017, OR: 1.9, 95%CI 1.1-3.3) were more likely to experience an increase of SDI during the follow-up (Table II ). Conclusions: Our data demonstrate that: a) one-third of SLE patients have clinically significant aPL profiles; b) 21%, 42% and 57% of SLE patients have new organ damage in 5, 10 and 15 years; c) clinically significant aPL-profiles, older age at diagnosis, and male sex are associated with an increased risk of organ damage accrual during a fifteen year follow-up. Disclosure of Interest: None declared